2019
DOI: 10.5093/clysa2019a2
|View full text |Cite
|
Sign up to set email alerts
|

Reestructuración de las Creencias Asociadas al Consumo de Drogas y la Conducción en Jóvenes

Abstract: El reto de reducir los accidentes de tráfico y reforzar la seguridad vial hace necesario concienciar, especialmente a la población juvenil, de los riesgos que lleva asociado el binomio drogas y conducción. El objetivo de este estudio es analizar los efectos de la aplicación de un programa preventivo que pretende modificar las actitudes de los jóvenes frente a drogas y conducción, además de investigar la relación entre la percepción del riesgo del consumo de drogas y la conducción según la variable sexo. Se ha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 11 publications
4
10
0
Order By: Relevance
“…Global longitudinal strain has been studied extensively as a method to detect abnormal myocardial mechanics and has superior prognostic value to LVEF in predicting major adverse cardiac events and mortality (27)(28)(29)(30)(31)(32). While we found a higher prevalence of abnormal strain in patients with normal LVEF than other studies, the general observations of systolic dysfunction by SE in MIS-C patients with preserved LVEF are consistent with our results (10,11,23,24,33). The high prevalence of impaired strain in our cohort (86%) may arise from the clinical status of our patients being in the ICU with physiologic derangements consistent with more disease severity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Global longitudinal strain has been studied extensively as a method to detect abnormal myocardial mechanics and has superior prognostic value to LVEF in predicting major adverse cardiac events and mortality (27)(28)(29)(30)(31)(32). While we found a higher prevalence of abnormal strain in patients with normal LVEF than other studies, the general observations of systolic dysfunction by SE in MIS-C patients with preserved LVEF are consistent with our results (10,11,23,24,33). The high prevalence of impaired strain in our cohort (86%) may arise from the clinical status of our patients being in the ICU with physiologic derangements consistent with more disease severity.…”
Section: Discussionsupporting
confidence: 91%
“…Published case series have reported abnormal LVEFs in 34-80% of MIS-C patients, with median LVEF values ranging from 46% to 60% (1,8,10,11,(23)(24)(25). This mild degree of dysfunction is similar to our study, where the median LVEF in our abnormal EF group was 48.1% and all patients was 61.4%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A systematic review by Ahmed et al 37 showed the use of corticosteroids and IVIG in 52.3 and 76.2% of cases, respectively. Coronary artery abnormalities have been reported in 8 to 24% of the cases in studies done by Jain et al 22 and Valverde et al 38 Due to limited resource setting, echocardiography could not be done at our center so we could not assess coronary artery abnormalities in our cases.…”
Section: Discussionmentioning
confidence: 94%
“…16,17 Additionally, a statistically significant correlation between the severity of elevation in cardiac and biochemical domains and the need for intensive care support has been reported with regard to such diseases. 18 Given this, routine blood testing is the initial diagnostic tool in clinical situations due to its low cost and ease of use. More importantly, because platelets play a crucial role in the inflammatory response, the mean platelet volume (MPV), as evaluated by a complete blood count (CBC), can be used as an inflammatory marker.…”
mentioning
confidence: 99%